Convulsions in childhood malaria. - Wattanagoon, Y; Srivilairit, S; Looareesuwan, S; White, N (1994)
A retrospective survey was conducted of all 2911 children admitted with malaria to 4 provincial hospitals in eastern Thailand between 1977 and 1987. 96 (3.3%) had cerebral malaria of whom 21 (22%) died, 225 (7.7%) had convulsions but were not comatose (4 died), and 2590 were conscious and had no fits (5 died). Thus the relative risk of a fatal outcome associated with convulsions, in the absence of cerebral malaria, was 9.2 (95% confidence interval [CI] = 2.5-34.1), P = 0.004. Overall, Plasmodium falciparum caused 81% of infections, P. vivax 16%, and 3% were mixed. Convulsions without cerebral malaria were more common in children under 3 years old (16%) compared with older children (3%): relative risk 5.6 (95% CI = 4.2-7.5), and were significantly associated with falciparum malaria (8.3%) compared with vivax malaria (4.7%): relative risk 1.7 (95% CI = 1.1-2.7). Convulsions are an important complication of malaria in young children, and are associated specifically with P. falciparum infection, even in otherwise uncomplicated malaria.